TRANSIENT ANALYSIS OF A MICROSTRIP DIFFERENTIAL PAIR FOR HIGH-SPEED PRINTED CIRCUIT BOARDS (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
This paper analyzes the behavior of a microstrip differential pair manufactured on Rogers 4003 C substrate for high-speed printed circuit boards. The electromagnetic parameters of the structure are computed using the full-wave electromagnetic method; then the primary parameters are extracted and a circuit is built-in PSpice to analyze the transient regime. The influence of the propagation delay and the asymmetry of the input signals are simulated by choosing specific parameters of the input pulses.
Keywords: Transient analysis; Microstrip; Differential pair; High-speed printed circuit boards